Heart Failure And Type 2 Diabetes Mellitus: Neurohumoral, Histological And Molecular Interconnections - Ushakov, A.; Ivanchenko, V.; Gagarina, A. (Current Cardiology Reviews, 2023)
Heart failure (HF) is a global healthcare burden and a leading cause of morbidity and mortality worldwide. Type 2 diabetes mellitus (T2DM) appears to be one of the major risk factors that significantly worsen HF prognosis and increase the risk of fatal cardiovascular outcomes. Despite a great knowledge of pathophysiological mechanisms involved in HF development and progression, hospitalization rates in patients with HF and concomitant T2DM remain elevated. In this review, we discuss the complex interplay between systemic neurohumoral regulation and local cardiac mechanisms participating in myocardial remodeling and HF development in T2DM with special attention to cardiomyocyte energy metabolism, mitochondrial function and calcium metabolism, cardiomyocyte hypertrophy and death, extracellular matrix remodeling.
Keywords: cardiac remodeling